Analysis of Women Traders’ Approaches to Resilience During the Outbreaks of Covid 19 - Suharta, Robertus Belarminus; Septiarti, Serafin Wisni; Kusumawardani, Erma; Santi, Fitta Ummaya; Syamsi, Ibnu (Universitas Negeri Semarang, 2023)
Gender disparities still exist in the business world, yet things are slowly starting to change. Other than that, women have historically faced greater obstacles than men when it comes to achieving success in the business world. Women are becoming leaders in industries and achieving top positions in companies. This paper describes the result of need analysis of women's capacity development strategy among the actors of the community-based creative economy in tourism business. This qualitative approach used observation, interviews with focused group discussion activities, and document analysis as a method to collect data. It was carried out involving 25 women creative economy actors as informants. Business pattern dynamization emerged as one of the strategies to cope with socio-economic issues due to the pandemic, which was done by developing businesses in an agricultural field, fulfilling household needs, online ready-made garments, and opening a business at the beach. The community serves as a social capital that helps creative economy actors in this study overcome hindrances, such as high-interest loans, price war, and unhealthy competition. Hence, these women embody the qualities of resilience, determination, and grit. They prove that with hard work and dedication, anything is possible.